ZX: A network file system for high‐latency networks. (18th October 2017) - Ballesteros, Francisco J.; Guardiola, Gorka; Soriano, Enrique
Summary: Using a central file server is good for interactive access to files, because of the coherency implied by a centralized design. In fact, within local area networks, this is a common case. However, distributed environments in use today may exhibit round‐trip times on the order of 50 or 100 ms. This is a problem for interactive file access to a central file server because of the resulting access times. Although aggressive caching and loosely synchronized replicas may be used for distributed file access, there are cases where the better coherency provided by a central server is still desirable. In this paper, we present ZX, a distributed file system and protocol designed with latency in mind. It can use caching, but it does not require caching or batching to address latency issues. ZX relies on a novel channel‐based file system interface. It includes find requests and leverages streaming requests to work well under high‐latency conditions. Unlike other protocols designed for distributed access to a central server, ZX tolerates round‐trip times on the order of 50 or 100 ms to access a central file server for interactive usage such as compiling shared sources, running binaries, editing documents, and other similar workloads. It can be used on UNIX using a FUSE adaptor while permitting native ZX speakers to run faster.